High density lipoprotein coated calcium carbonate nanoparticle for chemotherapy of breast cancer. (August 2019) - Wei, Kai; Zhang, Jiaming; Li, Xun; Shi, Pengfei; Fu, Peng
Satisfactory chemotherapy of breast cancer remains to be a great challenge in both experimental and clinical practice. Here in our study, we successfully developed a mixed drug delivery system composed of high density lipoprotein and calcium carbonate nanoparticles. The well-defined calcium carbonate nanoparticles served as a skeleton material to load anticancer drug doxorubicin, while high density lipoprotein served as a coating material to increase the stability and biocompatibility of the as-prepared mixed drug delivery system. Our experimental results indicated that the doxorubicin loading efficiency of HDL/CC nanoparticles was relatively high that is beneficial for the following administration. On the other hand, drug loaded HDL/CC/DOX nanoparticles can increase the uptake ratio of doxorubicin into breast cancer cells (MCF-7) compared with bare CC/DOX nanoparticles. Moreover, the in vivo tumor homing ability of HDL/CC nanoparticles as also superior than bare CC/DOX nanoparticles. Thus, HDL/CC/DOX nanoparticles exhibited stronger anticancer activity in vitro than free DOX or CC/DOX nanoparticles with minimized toxic side effects and preferable tumor-suppression capability on tumor-bearing nude mice model, which holds the potential to be further developed as a promising drug delivery system to be administered in clinic.